Perceived economic situation and related policies influence the entrepreneurial intentions of vocational college students, evidence from China - Jia, Guo; Khatibi, Ali; Tham, Jacquline (Edelweiss Applied Science and Technology, 2025)
Vocational college students' entrepreneurship is important for economic growth. Vocational college students who receive higher education are expected to be the main drivers of entrepreneurship. However, in China, only 3% of graduates considered entrepreneurship as a career choice in 2023. Therefore, the factors influencing the intentions of vocational college students need further investigation. The study proposes a structural equation model (SEM) and collects 437 valid data points from five vocational colleges in China. The analysis was conducted using AMOS 28.0 and SPSS 28.0. The results indicate that perceived economic situation (β = 0.345, p < 0.001) and related policies (β = 0.348, p < 0.001) positively influence entrepreneurial intentions. Additionally, perceived economic situation (β = 0.324, p < 0.001) and related policies (β = 0.356, p < 0.001) positively influence attitudes toward entrepreneurship. The attitudes toward entrepreneurship partially mediate the relationship between perceived economic situation, related policies, and entrepreneurial intentions among vocational college students. This study advances the Theory of Planned Behavior (TPB) and enriches the application of Entrepreneurial Ecosystem Theory (EET). It also provides implications for entrepreneurship education.